Examination of the shoulder in the overhead and throwing athlete - McFarland, E. G.; Tanaka, M. J.; Papp, D. F. (Clinics in Sports Medicine, 2008)
The advent of arthroscopy and the scientific study of the efficacy and accuracy of that examination have led to important advances in our understanding of the shoulder examination in the overhead and throwing athlete. In this review, we address current physical examination techniques and how to perform them, and explore their reported clinical efficacy, providing the practicing clinician with a better understanding of the proper application and interpretation of the shoulder examination in the overhead and throwing athlete.